2019
DOI: 10.1007/s13205-019-1662-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mixed cultures of Candida tropicalis and aromatizing yeast in alcoholic fermentation on the quality of apple vinegar

Abstract: There are two steps (alcoholic fermentation and acetic acid fermentation) in the production of fruit vinegar by liquid fermentation. The yeast alcoholic fermentation step plays an important role in the quality of apple vinegar. In this work, Candida tropicalis and aromatizing yeast were used in mixed alcoholic fermentation to improve the flavor of the apple vinegar. The total organic acid contents of apple cider and vinegar in mixed cultures were all higher than those in pure culture (Candida tropicalis). Umam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…PCA analysis has been applied to investigations of the composition of volatile compounds in vinegars produced from red wine and apples (CALLEJÓN et al, 2009;LIU et al, 2019). It has also been applied to the correlation between grape variety or geographical location in fine wines (OLIVEIRA et al, 2011), for characterizing the mineral content of wine vinegars (GUERRERO et al, 1997), and for analyzing the chemical composition and antioxidant characteristics of traditional and industrial Zhenjiang vinegar during the aging process (ZHAO et al, 2018).…”
Section: Principal Component Analysis (Pca) Of Mangaba Vinegarmentioning
confidence: 99%
“…PCA analysis has been applied to investigations of the composition of volatile compounds in vinegars produced from red wine and apples (CALLEJÓN et al, 2009;LIU et al, 2019). It has also been applied to the correlation between grape variety or geographical location in fine wines (OLIVEIRA et al, 2011), for characterizing the mineral content of wine vinegars (GUERRERO et al, 1997), and for analyzing the chemical composition and antioxidant characteristics of traditional and industrial Zhenjiang vinegar during the aging process (ZHAO et al, 2018).…”
Section: Principal Component Analysis (Pca) Of Mangaba Vinegarmentioning
confidence: 99%
“…Os componentes do aroma são indicadores importantes da qualidade do vinagre de maçã. O sabor característico é determinado pelo tipo, quantidade e interações entre os componentes (Liu et al 2019). O vinagre de maçã possui propriedades medicinais e benefícios gerais para a saúde.…”
Section: Introductionunclassified
“…Usually, biovinegar production utilizes specific microorganism strain for the fermentation to occur. However, it has been reported that biovinegar from single strain fermentation is inferior to that from the mixed strains (Liu et al, 2019). The use of mixed strain together with the carry over benefit of the raw materials were seen to improve the aroma and quality of biovinegar (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that biovinegar from single strain fermentation is inferior to that from the mixed strains (Liu et al, 2019). The use of mixed strain together with the carry over benefit of the raw materials were seen to improve the aroma and quality of biovinegar (Liu et al, 2019). Study by Liu et al (2019) and Chen et al (2017) proved that mixed strains apple and citrus biovinegar were rich in flavour, aroma and antioxidant activity than its single strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation